Analysis of genetic polymorphisms of TBX5, NKX2-5 and GATA4 cardiac transcription factor genes in Malaysian non syndromic congenital heart disease subjects - Khadhim, Nora F. (2012)
Congenital heart disease (CHD) is the most common congenital anomaly of the new born infants. The underlying etiology of CHD is unrecognized in the majority of cases. Cardiac transcription factor genes have a crucial role in the cardiogenesis process during the embryonic period, hence a number of single nucleotide polymorphisms (SNPs) have been identified to cause CHD in many populations but there have been no studies that had been found among Malaysian CHD subjects. Hence, this study was initiated to determine the allelic and genotypic frequencies of three important polymorphisms of cardiac transcription factor genes, namely the intronic polymorphism rs11067075 of TBX5 gene, R25C of NKX2-5 gene and G296S of GATA4 gene. We conducted a cross-sectional unmatched genetic association study between cases with CHD and healthy control subjects to determine the association of these polymorphisms and their genotype-phenotype correlation. A total of 150 non syndromic CHD subjects and 150 normal healthy individuals were recruited to this study with no matching for age and gender between cases and controls. We designed a protocol for genotyping of those three polymorphisms by real time-PCR-high resolution melt (HRM) analysis. Our study results shows that, the frequency of the polymorphism rs11067075 of TBX5 gene was 4.7% in CHD subjects versus a frequency of 0.7% in the healthy controls showed a significant association with the development of CHD (p<0.05). NKX2-5 gene heterozygote R25C (c.73.C>T) polymorphism was totally absent from both the cases and the control groups while genotyping of this polymorphism was incidentally accompanied by genotyping of a common variant of NKX2-5 gene (c.63A>G). Nevertheless, the genotype and allele frequencies of the polymorphism c.63A>G of NKX2-5 gene showed no difference between the cases and control groups (p=0.893). GATA4 gene heterozygote G296S polymorphism was also not detected in this study cohort. The association of TBX5 gene intronic polymorphism (rs11067075) with the development of CHD in this study emphasizes the role of TBX5 gene in the pathogenesis of non-syndromic CHD. The selected polymorphisms of NKX2-5 gene (R25C) and GATA4 gene (G296S) were not associated with the development of CHD in Malaysian subjects. However, investigating GATA4 and NXK2-5 genes in a bigger sample size for different variants might reveal an association of those gene polymorphisms with the development of CHD in Malaysian subjects. High resolution melting (HRM) analysis was used as a new technology for detecting those polymorphisms and had shown its power in an efficient genotyping and had the advantage of simultaneous genotyping and screening for sequence variants of R25C of NKX2-5 gene.